"THE ROLE OF FATHER AND MOTHER IN RAISING A GIRL" - Djurabaeva Ziroat Anvarovna (Galaxy International Interdisciplinary Research Journal, 2022)
In the article, raising a girl from birth to 3 years old, shaping a girl’s personality from 3 to 5 years old, how to educate girls, mutual trust and care, how to educate girls, in the mind of a girl, the educator is put in the place of the father.